Unmasking malignancy of lung nodule using a modernized ConvNet toward the design of a vision transformer - Reza, Jamil Ur; Tannee, Khadiza Siddique; Orpa, Sanjana Maruf; Fahim, Hasan Mahmud; Foysal, Riyad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.